Giant cell tumor of bone – Analysis of 213 cases involving extra‐craniofacial bones. Issue 8 (14th June 2021) - Konishi, Eiichi; Outani, Hidetatsu; Mano, Masayuki; Nagata, Shigenori; Shirai, Toshiharu; Naka, Norifumi; Hori, Yumiko; Takenaka, Satoshi; Haga, Hironori; Toguchida, Junya; Kakunaga, Shigeki; Kuwae, Yuko; et al.
Abstract: We elucidated clinicopathological characteristics of giant cell tumor of bone (GCTB) in Japan, and significant clinicopathological factors for predicting local recurrence. Clinicopathological profiles of 213 patients with GCTB (100 male, 113 female) involving extra‐craniofacial bones were retrieved. Pathological slides obtained at the initial surgery were reviewed. Fourteen pathological and five clinical features were statistically analyzed to disclose prognostic significance. Patient age ranged from 12–80 years (Average 38.7). Long bones were most frequently affected (86.4%), especially around the knee (62.9%). Histological features are basically similar to those previously reported. Within a follow‐up period (24–316 months, average 106.1 months), the local recurrence rate is 29.1%. Metastasis has occurred in 9 patients. Cox regression analysis of representative clinicopathological features shows that younger age, higher mitotic count, smaller zones of stromal hemorrhage, considerable vascular invasion and absence of ischemic necrosis are significant predictors for local recurrence. Initial operative method (curettage) is a significant risk factor in univariate analysis but not by multivariate analysis ( P = 0.053). Denosumab administration increases risk but not significantly ( P = 0.053). Histone 3.3 G34W immunopositivity is not significant for predicting local recurrence.